Preterm birth and the risk of chronic disease multimorbidity in adolescence and early adulthood: A population-based cohort study. - Katriina Heikkilä; Anna Pulakka; Johanna Metsälä; Suvi Alenius; Petteri Hovi; Mika Gissler; Sven Sandin; Eero Kajantie (PLoS ONE, 2021)
Background People who were born prematurely have high risks of many individual diseases and conditions in the early part of the life course. However, our knowledge of the burden of multiple diseases (multimorbidity) among prematurely born individuals is limited. We aimed to investigate the risk and patterns of chronic disease multimorbidity in adolescence and early adulthood among individuals born across the spectrum of gestational ages, comparing preterm and full-term born individuals. Methods and findings We used individual-level data from linked nationwide registers to examine the associations of gestational age at birth with specialised healthcare records of ≥2 chronic diseases (multimorbidity) in adolescence (age 10-17 years) and early adulthood (age 18-30 years). Our study population comprised 951,116 individuals (50.2% females) born alive in Finland between 1st January 1987 and 31st December 2006, inclusive. All individuals were followed from age 10 years to the onset of multimorbidity, emigration, death, or 31 December 2016 (up to age 30 years). We estimated hazard ratios (HRs) and 95% confidence intervals (CIs) for multimorbidity using flexible parametric survival models. During 6,417,903 person-years at risk (median follow-up: 7.9 years), 11,919 individuals (1.3%) had multimorbidity in adolescence (18.6 per 10,000 person-years). During 3,967,419 person-years at risk (median follow-up: 6.2 years), 15,664 individuals (1.7%) had multimorbidity in early adulthood (39.5 per 10,000 person-years). Adjusted HRs for adolescent multimorbidity, comparing preterm to full-term born individuals, were 1.29 (95% CI: 1.22 to 1.36) and 1.26 (95% CI: 1.18 to 1.35) in females and males, respectively. The associations of preterm birth with early adult multimorbidity were less marked, with the adjusted HRs indicating 1.18-fold risk in females (95% CI: 1.12 to 1.24) and 1.10-fold risk in males (95% CI: 1.04 to 1.17). We observed a consistent dose-response relationship between earlier gestational age at birth and increasing risks of both multimorbidity outcomes. Compared to full-term born males, those born at 37-38 weeks (early term) had a 1.06-fold risk of multimorbidity in adolescence (95% CI: 0.98 to 1.14) and this risk increased in a graded manner up to 6.85-fold (95% CI: 5.39 to 8.71) in those born at 23-27 weeks (extremely premature), independently of covariates. Among females, the same risks ranged from 1.16-fold (95% CI: 1.09 to 1.23) among those born at 37-38 weeks to 5.65-fold (95% CI: 4.45 to 7.18) among those born at 23-27 weeks. The corresponding risks of early adult multimorbidity were similar in direction but less marked in magnitude, with little difference in risks between males and females born at 36-37 weeks but up to 3-fold risks observed among those born at 23-27 weeks. Conclusions Our findings indicate that an earlier gestational age at birth is associated with increased risks of chronic disease multimorbidity in the early part of the life course. There are currently no clinical guidelines for follow-up of prematurely born individuals beyond childhood, but these observations suggest that information on gestational age would be a useful characteristic to include in a medical history when assessing the risk of multiple chronic diseases in adolescent and young adult patients.